Influence of tribofilms on failures and friction of gears with particular focus on running-in. Issue 8 (14th October 2019) - Ziegltrum, Andreas; Emrich, Stefan; Lohner, Thomas; Michaelis, Klaus; Brodyanski, Alexander; Merz, Rolf; Kopnarski, Michael; Hoehn, Bernd-Robert; Stahl, Karsten
Abstract : Purpose: This paper aims to address the influence of tribofilms and running-in on failures and friction of gears. The operation regime of gears is increasingly shifted to mixed and boundary lubrication, where high local pressures and temperatures occur at solid interactions in the gear contact. This results in strong tribofilm formation due to interactions of lubricant and its additives with the gear flanks and is related to changes of surface topography especially pronounced during running-in. Design/methodology/approach: Experiments at a twin-disk and gear test rig were combined with chemical, structural and mechanical tribofilm characterization by surface analysis. Pitting lifetime, scuffing load carrying capacity and friction of ground spur gears were investigated for a mineral oil with different additives. Findings: Experimental investigations showed a superordinate influence of tribofilms over surface roughness changes on damage and friction behavior of gears. Surface analysis of tribofilms provides explanatory approaches for friction behavior and load carrying capacity. A recommendation for the running-in of spur gears was derived. Originality/value: Experimental methods and modern surface analysis were combined to study the influence of running-in and tribofilms on different failures and friction of spur gears.